Management education : implications for libraries and library schools; the 36th annual conference of the School, April 9-10, 1973 - Chicago. University. Graduate Library School (Chicago : University Studies in Library Science, 1973)
Papers in this volume were published originally in the Library Quarterly, Oct. 1973
Keywords: Library personnel management